(untitled) (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Enteric fever is a major public health problem in many developing countries including Bangladesh, where sanitation and public health standards are poor. Objectives: To study the socio-demographic, some of the epidemiological features and knowledge about typhoid vaccine of the hospitalized children with typhoid fever. Methods: This cross-sectional descriptive study was conducted in Bangladesh Shishu Hospital & Institute over a one year period from January to December, 2019. All diagnosed cases of Typhod fever admitted in Bangladesh Shishu Hospital & Institute, Dhaka fulfill the inclusion criteria were the study subjects. The informations were collected in a predesigned and pretested questionnaire which included sociodemographic data, family background and knowledge about Typhoid vaccine. Results: A total of 86 children were enrolled in this study who were diagnosed to have typhoid fever during one year period. More than 90% of patients were aged between 1 and 10 years. Majority (90%) of the parents of affected children were unaware about availability of effective vaccine against typhoid fever. An association between literacy status, socioeconomic status, level of personal hygiene and occurrence of typhoid fever was found. Conclusion: Public health interventions to minimize human carrier contact, improved personal hygienic measures and typhoid vaccination will help to reduce the morbidity and mortality of this global health problem. DS (Child) H J 2021; 38(1): 34-38